Rice-straw-based heat generation system compared to open-field burning and soil incorporation of rice straw: an assessment of energy, GHG emissions, and economic impacts - Migo-Sumagang, Maria Victoria P.; Maguyon-Detras, Monet Concepcion; Gummert, Martin; Alfafara, Catalino G.; Borines, Myra G.; Capunitan, Jewel A.; Van Hung, Nguyen (MDPI, 2020)
Rice is a staple food crop, and its production generates large volumes of agricultural waste, rice straw. Several studies have proven that open-field burning and soil incorporation are unsustainable practices of managing rice straw, but remain as prevalent methods of treating and disposing of rice straw. An alternative solution is to harness the energy from rice straw via a small-scale heat conversion system for paddy drying applications, which can reduce rice grain post-processing costs and improve paddy storage conditions. This study investigated the energy flow, Greenhouse Gas (GHG) emissions, and cost of a small-scale rice-straw-based heat generation (RBHG) system using a downdraft furnace and a dryer simulator setup. The highest input energy and GHG emissions of 92% and 68%, respectively, were from the heat generation stage. The RBHG energy ratio was between 1.4 and 1.7, and the percent net energy was between 39 and 67%. The best case of RBHG offers a possibility of a net GHG avoided (−61 kg CO2-eq Mg−1), while the worst case (856 kg CO2-eq Mg−1) has a net GHG emission comparable with soil incorporation. The average total cost of RBHG is 0.096 USD kWh−1. Overall, RBHG technology has the potential to improve energy flow, GHG emissions, and the cost of rice production systems.